Flow-simulated thrombin generation profiles as a predictor of thrombotic risk among pre-menopausal women - Jordan, Sumanas W.; Corriere, Matthew A.; Vossen, Carla Y.; Rosendaal, Frits R.; Chaikof, Elliot L. (Thrombosis and Haemostasis, 2012)
A large number of individuals are at risk for deep venous thrombosis (DVT) due to alterations in multiple coagulation factors and inhibitors secondary to malignancy, drug interactions, or other general medical conditions. Traditional metrics of haemostasis such as prothrombin time, partial thromboplastin time, and bleeding time, generally estimate anticoagulation status and bleeding risk rather than thrombosis risk. The objective of this study was to correlate a novel, systems-based metric of clotting potential to risk of DVT from a database derived from the Leiden Thrombophilia Study (LETS). We utilised a computational model of blood coagulation, which addresses the interplay between biochemical factors, blood flow, and physiologic surface initiation of coagulation, to calculate an individualised, systems-based metric of clotting potential, termed the flow-simulated thrombin generation (FSTG), for 210 pre-menopausal women in LETS. Both DVT and oral contraceptive (OC) use were associated with higher values of FSTG. We demonstrated a nearly three-fold increased risk of DVT for each standard deviation increase above the mean in FSTG determined under venous flow conditions, which remained highly predictive after adjustment for age and OC status (adjusted odds ratio 2.66; 95% confidence interval 1.69–4.19; p<0.0001). In conclusion, a systems-based screening approach that integrates biochemical factors and flow haemodynamics identifies small subgroups of patients at risk of thrombosis that may benefit from oral anticoagulants.
Keywords: Thrombosis; blood coagulation; computer simulation; thromboembolism